Odpowiedź:
a)
A = (2 , - 3 ) , B = (5 , 6 )
xa = 2 , xb = 5 , ya = - 3 , yb = 6
IABI = √[(xb - xa)² + (yb - ya)²] = √[(5 - 2)² + (6 + 3)²] = √(3² + 9²) =
= √(27 + 81) = √108 = √(36 * 3) = 6√3
b)
A = (- 1 , - 8 ) , B = (3 , 7 )
xa = - 1 , xb = 3 , ya = - 8 , yb = 7
IABI = √[(xb - xa)² + (yb - ya)²] = √[(3 + 1)² + (7 + 8)²] = √(4² + 15²) =
= √(16 + 225) = √241
c)
A = (- 4 , 1 ) , B = (4 , - 3 )
xa = - 4 , xb = 4 , ya = 1 , yb = - 3
IABI = √[(xb - xa)² + (yb - ya)²] = √[(4 + 4)² + (- 3 - 1)²] = √[8² + (- 4)²] =
= √(64 + 16) = √80 = √(16 * 5) = 4√5
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Odpowiedź:
a)
A = (2 , - 3 ) , B = (5 , 6 )
xa = 2 , xb = 5 , ya = - 3 , yb = 6
IABI = √[(xb - xa)² + (yb - ya)²] = √[(5 - 2)² + (6 + 3)²] = √(3² + 9²) =
= √(27 + 81) = √108 = √(36 * 3) = 6√3
b)
A = (- 1 , - 8 ) , B = (3 , 7 )
xa = - 1 , xb = 3 , ya = - 8 , yb = 7
IABI = √[(xb - xa)² + (yb - ya)²] = √[(3 + 1)² + (7 + 8)²] = √(4² + 15²) =
= √(16 + 225) = √241
c)
A = (- 4 , 1 ) , B = (4 , - 3 )
xa = - 4 , xb = 4 , ya = 1 , yb = - 3
IABI = √[(xb - xa)² + (yb - ya)²] = √[(4 + 4)² + (- 3 - 1)²] = √[8² + (- 4)²] =
= √(64 + 16) = √80 = √(16 * 5) = 4√5